In Situ Fabrication of CdS/Cd(OH)2 for Effective Visible Light-Driven Photocatalysis - Ran Chen; Liping Qian; Shengyou Xu; Shunli Wan; Minghai Ma; Lei Zhang; Runren Jiang (Nanomaterials, 2023)
Photocatalytic hydrogen production is a promising technology that can generate renewable energy. However, light absorption and fast electron transfer are two main challenges that restrict the practical application of photocatalysis. Moreover, most of the composite photocatalysts that possess better photocatalytic performance are fabricated by various methods, many of which are complicated and in which, the key conditions are hard to control. Herein, we developed a simple method to prepare CdS/Cd(OH)2 samples via an in situ synthesis approach during the photocatalytic reaction process. The optimal hydrogen generation rate of CdS/Cd(OH)2 that could be obtained was 15.2 mmol·h−1·g−1, greater than that of CdS, which generates 2.6 mmol·h−1·g−1 under visible light irradiation. Meanwhile, the CdS-3 sample shows superior HER performance during recycling tests and exhibits relatively steady photocatalytic performance in the 10 h experiment. Expanded absorption of visible light, decreased recombination possibility for photo-induced carriers and a more negative conduction band position are mainly responsible for the enhanced photocatalytic hydrogen evolution performance. Photo-induced electrons will be motivated to the conduction band of CdS under the irradiation of visible light and will further transfer to Cd(OH)2 to react with H+ to produce H2. The in situ-formed Cd(OH)2 could effectively facilitate the electron transfer and reduce the recombination possibility of photo-generated electron-hole pairs.